Risk factors for children requiring adenotonsillectomy and their impact on postoperative complications: a retrospective analysis of 2000 patients. (11th September 2019) - Gehrke, T.; Scherzad, A.; Hagen, R.; Hackenberg, S.
Summary: Adenotonsillectomies are commonly performed procedures and sleep‐disordered breathing is becoming increasingly important as an indication for surgery. Because of the higher risks in patients with obstructive sleep apnoea, the required level of postoperative care for these patients is currently under discussion, and better identification of patients at risk may reduce unnecessary postoperative monitoring. To evaluate the influence of obstructive sleep apnoea, and other risk factors, on peri‐operative complications in children requiring adenotonsillectomy, we performed a retrospective case‐control study that included 1995 patients treated between January 2009 and June 2017. In our analysis, young age (OR 3.8, 95%CI 2.1–7.1), low body weight (OR 2.6, 95%CI 1.5–4.4), obstructive sleep apnoea (OR 2.4, 95%CI 1.5–3.8), pre‐existing craniofacial or syndromal disorders (OR 2.3, 95%CI 1.4–3.8) and adenotonsillectomy, compared with adenoidectomy alone, (OR 7.9, 95%CI 4.7–13.1) were identified as risk factors for complications during or after surgery, p < 0.001. All 13 patients suffering from complications more than 3 h postoperatively had obstructive sleep apnoea plus at least one more of these risk factors. Patients at risk of postoperative complications can therefore be identified by several criteria pre‐operatively, and should be monitored postoperatively using pulse oximetry overnight. For all other patients, postoperative observation on a surgical ward without extra monitoring is sufficient. Admission to paediatric intensive care should be reserved for patients suffering serious intra‐operative complications.